2021
DOI: 10.3390/w13182545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodic Winter Irrigation on Salt Distribution Characteristics and Cotton Yield in Drip Irrigation under Plastic Film in Xinjiang

Abstract: Winter irrigation is an effective means of salt leaching, but the long-term effect on salinity is unclear. In 2008–2019, three different soil types of farmlands were selected as the study area by drip irrigation under film mulch combined with periodic winter irrigation in the non-growth period. The salinity of 0–150 cm as well as the survival rate and yield of cotton in the non-growth and growth periods were monitored, respectively. The mass fraction of soil salt decreased rapidly under winter irrigation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…According to the study of Liu et al [ 37 ], the difference in soil salinity spatial distribution under mulched drip irrigation only occurred in the crop growth period; the soil salinity was redistributed to a uniform state after stubble tillage. Therefore, proper flood irrigation is necessary for soil salt desalination during the crop’s non-growth period [ 5 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the study of Liu et al [ 37 ], the difference in soil salinity spatial distribution under mulched drip irrigation only occurred in the crop growth period; the soil salinity was redistributed to a uniform state after stubble tillage. Therefore, proper flood irrigation is necessary for soil salt desalination during the crop’s non-growth period [ 5 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical results showed large fluctuations in the main salt ions, which indicates that soil salt ions accumulated in the surface layer, under the influence of natural conditions and anthropogenic activities [43]. In addition, the ions SO 4 2− and Ca 2+ have low stressing effects on plants, and the ions Na + and Cl − have a more serious effects on plant growth [44,45].…”
Section: Statistical Analysis Of Soil Salinity Ions Ph and Sarmentioning
confidence: 99%
“…Elevation data were obtained from a dataset provided by the University of Bristol, UK, and the slope and aspect were calculated based on elevation data. Improper irrigation is one of the causes of secondary soil salinization [48,49], and studies have shown that salts accumulate easily in districts where irrigation canals are dense [45]. In addition, there is a close connection between the distance to the drainage canal and soil salinity; irrigation systems and drainage systems have an impact on salinization through agricultural water abstraction and drainage activities [50,51].…”
Section: The Influencing Factors Of Soil Salinitymentioning
confidence: 99%
“…Therefore, proper flood irrigation was necessary for soil salt desalination during crop non-growth period (Liu et al 2013;Feng et al 2021;Zhang et al 2020).…”
Section: Soil Salt Accumulation With Soil Moisture Lower Limit Regula...mentioning
confidence: 99%